2002
DOI: 10.1080/09540120220123793
|View full text |Cite
|
Sign up to set email alerts
|

High risk sexual behaviours among heroin sniffers who have no history of injection drug use: Implications for HIV risk reduction

Abstract: The purpose of this paper is to assess sexual behaviours which place heroin sniffers (HSs) at high risk for HIV infection. A stratified network-based sample was used to recruit HSs who had no history of injection drug use was recruited from the streets of South Florida, USA. HSs displayed a high HIV seroprevalence rate of 12.1%; women (18.1%) were more likely than men (8.7%) to test positive for HIV. Both men and women HSs engaged in considerable high risk sex behaviour, including high risk sex-exchange behavi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
2

Year Published

2005
2005
2011
2011

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(46 citation statements)
references
References 9 publications
1
43
2
Order By: Relevance
“…For example, most studies found that physical QoL of symptomatic and AIDS patients is significantly poorer than that of patients who are at a lesser advanced stage of the disease [12,15,17,21,25,26,[33][34][35][36]. Associations between physical dimensions, but not psychological dimensions have also been shown in some studies [21,25,37]. Among the biological markers, higher CD4?…”
Section: Sociodemographic and Clinical Variablesmentioning
confidence: 89%
See 2 more Smart Citations
“…For example, most studies found that physical QoL of symptomatic and AIDS patients is significantly poorer than that of patients who are at a lesser advanced stage of the disease [12,15,17,21,25,26,[33][34][35][36]. Associations between physical dimensions, but not psychological dimensions have also been shown in some studies [21,25,37]. Among the biological markers, higher CD4?…”
Section: Sociodemographic and Clinical Variablesmentioning
confidence: 89%
“…Marital status provided some inconsistent associations. Most studies reported no differences [21,29], and others reported higher QoL among married patients, specially in the Social relationships domain [20,30]. One study [15] reported higher QoL among single patients.…”
Section: Sociodemographic and Clinical Variablesmentioning
confidence: 95%
See 1 more Smart Citation
“…This instrument, which took approximately 1-1.5 h to complete, included data on socio-demographics, drug use history, drug use networks, sex history, and criminal justice history. 10,36,37 Strict confidentiality was assured to all participants. After completion of the interview, HIV pre-test counselling was performed, and 10 ml of blood was drawn by venipuncture and tested for the presence of antibodies for HIV.…”
Section: Enrollment and Data Collectionmentioning
confidence: 99%
“…Sexual health-related diseases within addict populations have raised awareness of the effects of drugs of abuse on sexual behavior, as chronic drug use is associated with unsafe sexual practices resulting in increased prevalence of sexually transmitted infections, including human immunodeficiency virus (HIV) (Crowe and George, 1989;Peugh and Belenko, 2001;Sánchez et al, 2002;Raj et al, 2007;Fisher et al, 2011). These effects of drugs on sexual behavior are well documented for the psychostimulant methamphetamine (Meth).…”
Section: Introductionmentioning
confidence: 99%